2014
DOI: 10.1111/ajt.12515
|View full text |Cite
|
Sign up to set email alerts
|

Natural CD8+CD122+ T Cells Are More Potent in Suppression of Allograft Rejection Than CD4+CD25+ Regulatory T Cells

Abstract: Despite extensive studies on CD4þCD25þ regulatory T cells (Tregs), their application in adoptive transfer therapies is still not optimal in immune-competent wild-type (WT) animal models. Therefore, it is compelling to search for more potent Tregs for potential clinical application. Mounting evidence has shown that naturally occurring CD8þCD122þ T cells are also Tregs. However, their suppression in allograft rejection, efficiency in suppression and underlying mechanisms remain unclear. Using a murine allotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 35 publications
3
95
0
Order By: Relevance
“…Perhaps that is why we found that administration of IL-2 did not significantly promote CD8 1 CD122 1 Treg suppression of allograft rejection. 20 Instead, we demonstrated that administration of low doses of IL-15 promoted their homeostatic proliferation and enhanced their suppression of allograft rejection. 20 Taken together, both the B7/CD28 costimulatory and PD-L1/PD-1 coinhibitory pathways are required for optimal CD8 1 CD122 1 Treg-mediated suppression, while IL-15 boosts their suppressive capacity via promoting their proliferation or expansion.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Perhaps that is why we found that administration of IL-2 did not significantly promote CD8 1 CD122 1 Treg suppression of allograft rejection. 20 Instead, we demonstrated that administration of low doses of IL-15 promoted their homeostatic proliferation and enhanced their suppression of allograft rejection. 20 Taken together, both the B7/CD28 costimulatory and PD-L1/PD-1 coinhibitory pathways are required for optimal CD8 1 CD122 1 Treg-mediated suppression, while IL-15 boosts their suppressive capacity via promoting their proliferation or expansion.…”
Section: Introductionmentioning
confidence: 84%
“…20 Instead, we demonstrated that administration of low doses of IL-15 promoted their homeostatic proliferation and enhanced their suppression of allograft rejection. 20 Taken together, both the B7/CD28 costimulatory and PD-L1/PD-1 coinhibitory pathways are required for optimal CD8 1 CD122 1 Treg-mediated suppression, while IL-15 boosts their suppressive capacity via promoting their proliferation or expansion. However, it remains unknown whether CD8 1 CD122 1 Tregs can modulate antigen-presenting cells, which in turn, regulate aggressive effector CD4 1 or CD8 1 T cells.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Maternal CD8 + T cell responses can also affect placental function (40)(41)(42). Recent studies in mouse models have indicated that the presence of the naturally occurring CD8 + T cell subset CD8 + CD122 + T cells is capable of suppressing inflammation in autoimmunity, transplantation, and other inflammatory conditions (43)(44)(45). However, to date, the mediators involved in the generation of CD8 + CD122 + T cells and their functional role in pregnancy maintenance remain unknown.…”
Section: Introductionmentioning
confidence: 99%